2018
DOI: 10.3390/jdb6030019
|View full text |Cite
|
Sign up to set email alerts
|

Heart Development, Coronary Vascularization and Ventricular Maturation in a Giant Danio (Devario malabaricus)

Abstract: Giant danios (genus Devario), like zebrafish, are teleosts belonging to the danioninae subfamily of cyprinids. Adult giant danios are used in a variety of investigations aimed at understanding cellular and physiological processes, including heart regeneration. Despite their importance, little is known about development and growth in giant danios, or their cardiac and coronary vessels development. To address this scarcity of knowledge, we performed a systematic study of a giant danio (Devario malabaricus), focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…We have recently reported on the breeding, rearing, cardiac development, and coronary vasculature of the D . malabaricus . In the course of these studies, we observed unexpected adhesive behaviors and a cement gland.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…We have recently reported on the breeding, rearing, cardiac development, and coronary vasculature of the D . malabaricus . In the course of these studies, we observed unexpected adhesive behaviors and a cement gland.…”
Section: Introductionmentioning
confidence: 75%
“…Experimental procedures were approved by the Committee for the Care and Use of Laboratory Animals at DePauw University. The breeding of the D. malabaricus has previously been published . Briefly, adult D. malabaricus 50‐60 mm in standard length from Segrest Farms (Gibsonton, Florida) were first acclimated to 28.5°C for 1‐3 weeks prior to breeding.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations